Characterization of sheep and goat farming cut in the Central North Baiano - Porto, Leila Lopes da Mota Alves (2013)
The main objective of this study was to characterize the Sheep and Goat Farming in the region of cutting Jussara in the state of Bahia, in its structure which identifies the main barriers and bottlenecks to the development of activity in the region. The methodology adopted was case study, both qualitative and quantitative sampling and intentional, considering the concentration of cooperators and suppliers of local Cooperative - Cooperative of Rural Entrepreneurs Jussara (COPERJ). To obtain the primary data were applied at random, semi-structured questionnaires for two segments of the chain under study: COPERJ and producers. It was found that the productive chain of the Sheep and Goat Farming in the region is well structured compared to other regions of the Northeast, where producers are organized around and Cooperative Associations, and the flow of production occurs through COPERJ, slaughterhouse regional, independent buyers (middlemen), regional markets and butcher shops, but with higher opportunism among the chain actors. The socioeconomic profile of producers, it was observed that the majority is made up of small landowners dominated the use of family labor and extensive system of animal husbandry, with greater participation of sheep. The administration of the properties is still unprofessional, with little technical assistance and rural extension for production and management, and participation of producers in programs such as Bolsa Familia and Pronaf contributes to income generation and improvement of properties. Still, the producers have demonstrated safety and confidence in COPERJ and future of the Sheep and Goat Farming in the region.